Chronic Treatment with Sildenafil Stimulates Bone Regeneration in a Calvarial Bone Defect in Rats - Brenna, Esteban Matías (2020)
Fil: Brenna, Esteban Matías. Universidad Nacional de Córdoba. Facultad de Odontología. Departamento de Biología Bucal; Argentina.